2008
DOI: 10.1111/j.1469-8137.2008.02584.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient xylem transport of arsenite in the arsenic hyperaccumulator Pteris vittata

Abstract: Summary• The hyperaccumulator Pteris vittata translocates arsenic (As) from roots to fronds efficiently, but the form of As translocated in xylem and the main location of arsenate reduction have not been resolved.• Here, P. vittata was exposed to 5 µM arsenate or arsenite for 1-24 h, with or without 100 µM phosphate. Arsenic speciation was determined in xylem sap, roots, fronds and nutrient solutions by high-performance liquid chromatography (HPLC) linked to inductively coupled plasma mass spectrometry (ICP-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(113 citation statements)
references
References 31 publications
5
102
2
1
Order By: Relevance
“…And, considering the much higher As concentration in the endodermis and vascular bundle in the long timescale (Fig. 5), it was deduced that As(III) may have been more easily transported from the endodermis to vascular bundle than As(V), in agreement with Su et al (2008). In rice and microorganisms, including Escherichia coli and yeast (Saccharomyces cerevisiae), it has been observed that As is transported as As(III) through a silicon transporter belonging to a subfamily of aquaporins (Ma et al, 2008;Porquet and Filella, 2007).…”
Section: Scanning Sitesupporting
confidence: 64%
“…And, considering the much higher As concentration in the endodermis and vascular bundle in the long timescale (Fig. 5), it was deduced that As(III) may have been more easily transported from the endodermis to vascular bundle than As(V), in agreement with Su et al (2008). In rice and microorganisms, including Escherichia coli and yeast (Saccharomyces cerevisiae), it has been observed that As is transported as As(III) through a silicon transporter belonging to a subfamily of aquaporins (Ma et al, 2008;Porquet and Filella, 2007).…”
Section: Scanning Sitesupporting
confidence: 64%
“…Previous studies have shown that As(III) dominates in the xylem sap collected from a number of plant species exposed to As(V), including tomato, rice, cucumber, and the As hyperaccumulator P. vittata (Mihucz et al, 2005;Xu et al, 2007;Su et al, 2008Su et al, , 2010. In contrast, As(V) was found to be an important As species in the xylem sap collected from B. juncea, Holcus lanatus, and wheat, accounting for between 30% to 60% of the total As (Pickering et al, 2000;Su et al, 2010).…”
Section: Discussionmentioning
confidence: 69%
“…O arsenato absorvido pela planta é reduzido a arsenito, que tem elevada afinidade com os grupos tiol de peptídeos (HUANG et al, 2008;MELENDEZ, 2006;SNELLER et al, 1999;SRIVASTAVA;MA;SANTOS, 2006;ZHAO et al, 2008). A complexação de arsenito por tióis é um importante mecanismo de desintoxicação de As, podendo diminuir a sua translocação, especialmente se os complexos forem sequestrados nos vacúolos de células radiculares (SU et al, 2008). A elevada translocação de As na quaresmeira pode ser resultado da baixa capacidade de complexação do metaloide nas células radiculares.…”
Section: Resultsunclassified